Institutional responses to ChatGPT: Analysing the academic integrity policies of four public and private institutions of higher education in Australia - De Maio, Carmela (Journal of Academic Language and Learning, 2024)
ChatGPT and other generative artificial intelligence (GenAI) tools have disrupted teaching and learning in higher education and pose a potential threat to academic integrity. Although most tertiary institutions have in place policies on how to respond to breaches of academic integrity by students, these policies may not always be clear on how to best approach the potential impacts of GenAI to ensure academic integrity can be maintained. Consequently, this paper presents an analysis of the academic integrity policies and procedures of four Australian public and private institutions of higher education where I teach. Applying the elements of access, approach, responsibility, detail, and support from the framework developed by Bretag and her colleagues (2011), and including the additional elements of currency and flexibility, findings from document analysis of these policies suggests that not all of them contain all these elements so may not be effective enough to respond to the unauthorised use of ChatGPT by students. I argue that not only do policies need to be more regularly updated, but that more clarity and guidance is required for all stakeholders. Timely communication of relevant policy would be one way to maintain a positive culture of academic integrity in institutions of higher learning.